2020
DOI: 10.1101/2020.01.08.897009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sucrose promotes etiolated stem branching through activation of cytokinin accumulation followed by vacuolar invertase activity

Abstract: 16The potato (Solanum tuberosum L.) tuber is a swollen stem. Sprouts growing from the tuber 17 nodes represent dormancy release and loss of apical dominance. We recently identified 18 sucrose as a key player in triggering potato stem branching. To decipher the mechanisms by 19 which sucrose induces stem branching, we investigated the nature of the inducing molecule 20 and the involvement of vacuolar invertase (VInv) and the plant hormone cytokinin (CK) in 21 this process. Sucrose was more efficient at enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…It was demonstrated that CTK synergistically induces the production of extracellular invertase and hexose transporters, which are functionally coupled to provide carbohydrates to sink tissues and are involved in phloem unloading (Roitsch and Ehne, 2000). It was reported that sugar-induced lateral bud outgrowth was in part, promoted by the induction of CTK-mediated vacuolar invertase activity (Salam et al, 2021). Previous research showed significant differences in stubble dry weight and NSC content at the maturity stage of the main crop under the different leaf-cutting and spikelet-thinning treatments (He et al, 2019).…”
Section: Leaf Cutting Treatmentmentioning
confidence: 99%
“…It was demonstrated that CTK synergistically induces the production of extracellular invertase and hexose transporters, which are functionally coupled to provide carbohydrates to sink tissues and are involved in phloem unloading (Roitsch and Ehne, 2000). It was reported that sugar-induced lateral bud outgrowth was in part, promoted by the induction of CTK-mediated vacuolar invertase activity (Salam et al, 2021). Previous research showed significant differences in stubble dry weight and NSC content at the maturity stage of the main crop under the different leaf-cutting and spikelet-thinning treatments (He et al, 2019).…”
Section: Leaf Cutting Treatmentmentioning
confidence: 99%
“…We previously hypothesized that CK levels are important to promote bud outgrowth when sugars are not readily available for buds (Barbier et al, 2019b). Accordingly, CK has been reported to promote nutrient sink strength (Roitsch & Ehneß, 2000;Werner et al, 2008;Peleg et al, 2011;Wang et al, 2016), and it was recently reported that thus sugarinduced bud outgrowth in dark-grown potato sprouts was mediated, at least partly, by a CK-induced invertase activity (Salam et al, 2020). In this view, we would expect that cytokinin synthesis mutants would indeed have a reduced response to decapitation which enhances sucrose availability.…”
Section: Hexokinase1 Interacts With Cytokinin and Strigolactone Pathways To Support Shoot Branchingmentioning
confidence: 99%
“…Axillary buds require a source of sugar to grow out, and the strong demand for sugar by the shoot apex inhibits axillary bud outgrowth (Mason et al, 2014; Barbier et al, 2019). During shoot branching, sugars were reported to promote cytokinin synthesis and inhibit strigolactone perception (Barbier et al, 2019; Bertheloot et al, 2020; Salam et al, 2020; Patil et al, 2021). Despite the detailed knowledge of molecular physiological mechanisms, translating these discoveries into breeding outcomes is still a challenge.…”
Section: Introductionmentioning
confidence: 99%